Belief in Religious Values for the Chinese Community in Sri Tanjung Village, Siantan District, Anambas Regency - Said Muhammad Khairul Nizam; Sri Wahyuni; Siti Arieta (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2023)
The concept of value in religion is basic knowledge in the form of teachings that originate from God Almighty. These values include thoughts, beliefs, morals, and everything that is oriented towards how a person is able to implement religious values in life. In this study, the focus is on the Chinese community and how they implement religious values in Sri Tanjung Village, Siantan District, Anambas Regency. The purpose of this study is to describe their practices. Qualitative research methods with a descriptive approach were used for this study. The results of this study found that the Chinese community in Sri Tanjung Village, Siantan District, Anambas Regency implements religious values in their beliefs and practices. Their activities are based on ancestral principles and traits such as metta or love, karuna or affection, mudita or sympathy, and upekha or balanced mind. Moreover, they practice customs and culture that are still guarded from generation to generation, such as Chinese New Year culture, cap go meh, safar bathing, and the application of feng shui knowledge. Although many Chinese people continue to implement religious values, there are some who do not practice these religious practices. It was found that some Chinese people change their religion in order to get married in cases of interfaith marriage.